Does New Media Substitute Old Media? A Cohort Analysis of Media Use in China - Li, Weijia (Cultural and religious studies, 2020)
This study examines generational differences in media use based on pooled-data analysis of CGSS (Chinese General Social Survey) 2010-2015. In order to show a full picture of the substitutability between new and old media, the study brings age heterogeneity of respondents and time effect into consideration. This study distinguishes four generations based on the year of birth, with the "newspaper generation" (people who born before 1969), "broadcast generation" (1970-1979), "TV generation" (1980-1989), and "Internet generation" (born after 1990) and aims to explore whether generations differ in their frequency of media use. The research analyses five-year pooled data CGSS 2010-2015 (CGSS 2014 data is missing) to examine the influence of Internet on old media among different birth cohorts and how this effect changes over time. New media refers to the Internet; old media includes newspaper, broadcast, and television. The results are summarized as follows: First, for the "newspaper generation", "broadcast generation", and "TV generation", Internet heavy users are usually more willing to use newspaper and broadcast as well. Internet heavy users are information seekers. They have a strong need of information and usually are involved in multi-tasking media activities. Nevertheless, only the Internet heavy users in "TV generation" will regard TV as another channel to get more information, which indicates that generations may adopt specific patterns of media use when they are young and remain faithful to those throughout their lifespans. "TV generation" have a stronger attachment to television than their previous and later generation. Second, in terms of the time effect, the empirical data proved that the broadcast shows a stronger vitality in digital age compared with newspaper and television. The frequency of broadcast use does not drop significantly until 2015. However, the frequency of newspaper and television use has shown a significant downward trend since 2011. Third, for the "Internet generation", the use of the Internet has no effect on the use of other media. Even Internet heavy user, the one who has strong need of information, would not choose other media to search more information. This suggests that these digital natives would rather confine themselves to the Internet cocoon than collect new information through old channels. This study provides new insight to understand the current media ecology. The relationship between the new and the old media is a changeable and dynamic process and cannot be simply understood as "more-more" or "more-less" relationship.